Between Entertainment and Rest: The Role of Self-regulation in Overcoming Bedtime procrastination Among Working College Students - Tasya Ulfaningsi; Hanny Rufaidah Damra (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
Working students face a double burden of academic and work responsibilities, making them prone to bedtime procrastination. This study aims to examine the effect of self-regulation on bedtime procrastination among working students. A quantitative regression design was employed. Participants consisted of 175 active undergraduate students working part-time, recruited through purposive sampling. Data were analyzed using simple linear regression with IBM SPSS 27 version. The results indicate that self-regulation has a significant negative effect on bedtime procrastination among working students (F = 74.899; p < 0.001). The R² value of 0.302 indicates that self-regulation accounts for 30.2% of the variance in bedtime procrastination, while the remaining 69.8% is influenced by other variables not examined in this study. This means that the higher a working student’s self-regulation ability, the lower their tendency to delay going to sleep. These findings underscore the importance of developing self-regulation skills as a means to improve both the quality and quantity of sleep among working students.